2020
DOI: 10.1111/gbb.12717
|View full text |Cite
|
Sign up to set email alerts
|

The heritability of insomnia: A meta‐analysis of twin studies

Abstract: Twin studies of insomnia exhibit heterogeneity in estimates of heritability. This heterogeneity is likely because of sex differences, age of the sample, the reporter and the definition of insomnia. The aim of the present study was to systematically search the literature for twin studies investigating insomnia disorder and insomnia symptoms and to meta‐analyse the estimates of heritability derived from these studies to generate an overall estimate of heritability. We further examined whether heritability was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Insomnia was not highly coincident in monozygotic twins compared to dizygotic twins in this study. In twin studies based on young populations, the heritability of insomnia has been suggested with mixed results [ 6 , 8 , 21 , 22 ]. In a meta-analysis study, the correlation of insomnia was higher in monozygotic twins than in dizygotic twins (0.37, 95% CI = 0.31–0.43 for monozygotic twins and 0.15, 95% CI = 0.12–0.18 for dizygotic twins) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insomnia was not highly coincident in monozygotic twins compared to dizygotic twins in this study. In twin studies based on young populations, the heritability of insomnia has been suggested with mixed results [ 6 , 8 , 21 , 22 ]. In a meta-analysis study, the correlation of insomnia was higher in monozygotic twins than in dizygotic twins (0.37, 95% CI = 0.31–0.43 for monozygotic twins and 0.15, 95% CI = 0.12–0.18 for dizygotic twins) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple candidate genes for gene–environmental interactions in anxiety have been suggested [ 5 ]. Insomnia is one of the associated factors for anxiety, which also has heritability [ 6 , 7 , 8 ]. In a meta-analysis of twin studies, approximately 40% of heritable factors contributed to the occurrence of insomnia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not find significant differences in heritability between various insomnia symptoms, but noted there was a broad range between studies for difficulty initiating sleep (0-79%) and difficulty staying asleep (25-42%), with fewer studies evaluating early morning awakenings (34-35% in one study) and awakening tired (26% in one study). 14 Studies looking at pre-sleep arousal and sleep reactivity have also found substantial genetic overlap with insomnia, indicating possible enhanced vulnerability to insomnia occurring with these symptoms. A longitudinal twin and sibling study found a strong correlation between genetic influences on overall pre-sleep arousal and insomnia symptoms (genetic correlation = 0.88), as well as between cognitive pre-sleep arousal, somatic pre-sleep arousal, and insomnia symptoms (genetic correlations 0.93 to 1).…”
Section: Insomniamentioning
confidence: 99%
“…11 Numerous twin studies have identified the heritability, gene-environment interactions, and gene-environment correlations for both normal and pathologic sleep phenotypes. [12][13][14][15][16][17] Twin studies have also examined associations between sleep phenotypes and other health-related traits and disorder phenotypes, [18][19][20][21][22] many of which either impact sleep or are impacted by sleep. This provides an important body of work highlighting the complexity of genetic and environment interplay between sleep and health.…”
Section: Introductionmentioning
confidence: 99%